The Chain Rule formula is as follows:

If f(x)=g (h(x)), then f'(x)=g' (h(x)) h'(x).

Let me show you an example how to use this formula:

Example; Find derivative of f(x)= sin (3x^{2}+x).

Solution: In this question imagine f(x) is composed of two functions -- g(x)=sinx and h(x)=3x^{2}+x, and h(x) is the inner function in the formula. So according to the formula f'(x)=g' (h(x)) h'(x), we get this:

f'(x)=cos(3x^{2}+x) *(6x+1)=(6x+1) cos(3x^{2}+x)

Note that the derivative of sin x is cos x, that's why we get cos(3x^{2}+x), and (6x+1) is the derivative of 3x^{2}+x

**Subject :**Math**Topic :**Calculus-
**Posted By :**Jason **Created on :**07-26-2012

Privacy Policy |
Terms of Use and Policies |
Site Map |
Contact Us |
TutaPoint Blog |
Knowledge Center
Copyright 2007 - 2014 TutaPoint.com, All rights reserved.